2016
DOI: 10.1177/1934578x1601101130
|View full text |Cite
|
Sign up to set email alerts
|

Leonurine, a Potential Agent of Traditional Chinese Medicine: Recent Updates and Future Perspectives

Abstract: Herba Leonuri, also named Chinese Motherwort, has been extensively investigated as an effective agent on the uterus system. Our group has been studying the natural products of Herba Leonuri for several years, and during this period, many biological activities of the drug were recognized. Leonurine (4-guanidino- N-butyl-syringate) is an alkaloid present in Herba Leonuri. Recently, growing evidence has highlighted the therapeutic potential of leonurine in multiple diseases, especially cardiovascular. In this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Leonurine (YMJ), as an active ingredient, was first extracted as a TCM from Leonurus heterophyllus ( 18 ). YMJ promotes uterine contraction, and prevents osteoporosis, mastitis and myocardial fibrosis ( 19 ). The above functions of YMJ maybe associated with its anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%
“…Leonurine (YMJ), as an active ingredient, was first extracted as a TCM from Leonurus heterophyllus ( 18 ). YMJ promotes uterine contraction, and prevents osteoporosis, mastitis and myocardial fibrosis ( 19 ). The above functions of YMJ maybe associated with its anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%
“…Leonurine (C 14 H 21 N 3 O 5, 4-hydroxy-3, 5-dimethoxy, 4-[aminoiminomethyl) amino] butyl ester, the chemical structure shown in Fig. 1A), also known as benzoic acid, is an active alkaloid from food and a traditional Chinese medicine named Herba leonuri [13,14]. Modern pharmacological studies have reported that leonurine has a wide range of biological and pharmacological activities such as antioxidative, anti-inflammatory, antiapoptotic, anti-diabetic, and improving the circulatory system effects [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Leonurine (4-guanidino-n-butyl syringate, Figure 1 B) extracted from Chinese motherwort Herba leonuri is a natural alkaloid with immense traditional medicinal benefits, including treatment of gynecological, cardiovascular, nervous, cancer, uterine, and skin diseases [ 111 , 112 , 113 ]. The leaf shoot of H. leonuri reduces itching and was used to treat contagious skin diseases such as active shingles in ancient people [ 114 ].…”
Section: Natural Biomolecules Targeting Jak/stat/socs Signaling In Ad...mentioning
confidence: 99%